The Descartes dictionary - Smith, Kurt, 1961- (Bloomsbury philosophy dictionaries., 2015)
"The Descartes Dictionary is an accessible guide to the world of the seventeenth-century philosopher René Descartes. Meticulously researched and extensively cross-referenced, this unique book covers all his major works, ideas and influences, and provides a firm grounding in the central themes of Descartes' thought. The introduction provides a biographical sketch, a brief account of Descartes' philosophical works, and a summary of the current state of Cartesian studies, discussing trends in research over the past four decades. The A-Z entries include clear definitions of the key terms used in Descartes' writings and detailed synopses of his works. Also included are entries noting philosophical influences, of both figures that influenced Descartes and those that he in turn influenced. For anyone reading or studying Descartes, rationalism, or modern philosophy more generally, this original resource provides a wealth of useful information, analysis, and criticism. Including clear explanations of often complex terminology, The Descartes Dictionary covers everything that is essential to a sound understanding of Descartes' philosophy"--